Optimal mass scaling of power output for complex courses and its relationship to time-trial performance in cycling - Horvath, M.; Andersson, E. P. (Journal of Science and Cycling, 2025)
The allometric scaling of power output is a long-standing topic of debate in cycling research concerning performance prediction. In contrast to previously used test-based approaches, this study employed a numerical method to determine how external forces influence the conversion of power output into race velocity. Time-trial performances of typical elite-level road cyclist models were estimated utilizing the power-duration relationship and normative power data for two recent Grand Tour individual time-trial courses. Optimal body mass exponents were determined based on the estimated average speed of typical cyclists over the respective course sections, their morphological characteristics, and external factors such as incline and wind velocity. Estimated power output expressed in terms of optimally scaled power metrics - namely W/kg0.6068 and W/kg0.4891 - accurately predicted the estimated performance of five typical elite-level cyclists on two recent Grand Tour individual time-trial courses (for both). The study`s findings suggest that optimal mass exponents are course-specific and primarily influenced by the magnitude of headwind relative to the cyclist and the road gradient. Further field-based research is needed to validate the proposed method for determining these optimal mass exponents.